High Concentration of Aspirin Induces Apoptosis in Rat Tendon Stem Cells via Inhibition of the Wnt/β-Catenin Pathway - Wang, Yunjiao; Tang, Hong; He, Gang; Shi, Youxing; Kang, Xia; Lyu, Jingtong; Zhou, Mei; Zhu, Min; Zhang, Jiqiang; Tang, Kanglai (Cellular physiology and biochemistry, 2018)
Background/Aims: Non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used in clinical practice to relieve fever and pain. Aspirin, as a representative NSAID, has been widely used in the treatment of tendinopathy. Some reports have demonstrated that aspirin can induce apoptosis in cancer cells. However, evidence regarding aspirin treatment for tendinopathy, especially the effect of this treatment on tendon stem cells (TSCs), is lacking. Understanding the effect of aspirin on tendinopathy may provide a basis for the rational use of NSAIDs in clinical practice. The aim of our study was to determine whether aspirin induces apoptosis in rat TSCs via the Wnt/β-catenin pathway. Methods: First, we used flow cytometry and fluorescence to detect TSC apoptosis. Protein expression of the apoptosis-related caspase-3 pathway was investigated via western blot analysis. Next, we used western blotting to determine the effect of aspirin on the Wnt/β-catenin pathway. We used immunostaining to detect the levels of Bcl2, cleaved caspase-3, and P-β-catenin in the Achilles tendon. Finally, we used flow cytometry, fluorescence, and western blotting to investigate the aspirin-induced apoptosis of TSCs via the Wnt/β-catenin pathway. Results: Aspirin induced morphological apoptosis in rat TSCs via the mitochondrial/caspase-3 pathway and induced cellular apoptosis in the Achilles tendon. Apoptosis was partly reversed after adding the Wnt signaling activator Wnt3a and lithium chloride (LiCl, a GSK-3β inhibitor). Aspirin administration led to a dose-dependent increase in COX-2 expression. Apoptosis was promoted after adding the COX-2 inhibitor NS398. Conclusion: The Wnt/β-catenin pathway plays a vital role in aspirin-induced apoptosis by regulating mitochondrial/caspase-3 function. Elevating COX-2 levels may protect cells against apoptosis. More importantly, the results remind us to consider the apoptotic effect of aspirin on TSCs and tendon cells when aspirin is administered to treat tendinopathy. The relationship between the positive and negative effects of aspirin remains a subject for future study.